Algebra's Ripple Effect: How Enthusiasm for Algebra Shapes Students' Overall Attitudes Toward Mathematics - Ajai, John Tyavbee; Sanda, Hauwa; Abur, Cletus Terhemba (Journal of Research in Science and Mathematics Education, 2024)
Purpose: This study investigates the "ripple effect" of algebra, examining how students' enthusiasm or aversion to algebra influences their overall attitude toward mathematics. Methodology: The research employed a descriptive survey design and was conducted in the Gombe Education Zone, Nigeria, which includes 87 secondary schools. A sample of 500 students was selected through a multistage sampling technique across five local government areas. Data were collected using the Disposition of Students in Learning Algebra (DISLA), a 16-item instrument validated by experts and achieving a reliability index of 0.92 via Cronbach’s alpha. The DISLA consisted of two sections: sociodemographic data and students' perceptions of algebra. Research assistants administered the survey in the selected schools. Findings: The results, analyzed using frequency counts and percentages, revealed that 72.2% of students disliked specific mathematical topics, and only 29.9% found mathematics simple. Furthermore, 43.1% of students expressed a mild liking for algebra, while 42.3% showed a strong interest. Importantly, 50.7% believed their attitude toward algebra influenced their overall perception of mathematics. Significance: The study concludes that students' attitudes toward algebra significantly impact their engagement with and perception of mathematics, with positive attitudes fostering better performance. Recommendations include promoting a growth mindset, employing differentiated instruction, making mathematics more relevant to real-life applications, and addressing mathematics anxiety. Additionally, positive reinforcement and professional development for teachers are suggested to create a supportive learning environment, ultimately enhancing students' interest and performance in mathematics.